Animal-assisted physiotherapy: dog co-therapist as motivator and mediator of exercises for chronic patients (Research, Society and Development, 2020)
The implementation of a physical therapy protocol is essential to maintain the functionality of the elderly. The aim of this study was to evaluate the dog as a mediator and motivational factor in elderly patients with chronic diseases in face of animal-assisted physiotherapy (AAP) in an institution in the city of Pelotas. The qualitative and quantitative study was carried out between September and November 2019, with the participation of two dogs and five patients. There were seven sessions in average, which lasted 30 minutes and a protocol was established according to individual needs. As a method of evaluation, a questionnaire on the level of satisfaction was applied in the first and last session. Also, the scale of self-perception of happiness, heart rate and blood pressure were measured twice in each session. In conclusion, it was found that the dog was an ally in patients’ therapy promoting well-being and the AAP improved the patients’ emotional and physical conditions, as well as their proprioception and motor coordination.